Remembering slavery on screen: Paul Robeson in The Song of Freedom (1936) - Durkin, Hannah (Taylor & Francis, 2013)
This article examines cinematic remembrances of the Atlantic slave trade through the lens of Paul Robeson-starring British film The Song of Freedom (1936). An exceptional visualization of the horrors of the Middle Passage in transatlantic interwar cinema, the production nevertheless recapitulates an abolitionist visual paradigm characterized by lacunae and distortion. Yet, it also serves as an exploration of African independence driven by Robeson's self-reflexive performance, demand for script approval and stardom. Robeson's measure of authorial influence over the film represents a unique instance in British cinema in which a black performer was able to reframe dehumanizing representations of historical black experiences into a hopeful vision of an independent black future.